If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -4(p + -4) = 3p Reorder the terms: 12 + -4(-4 + p) = 3p 12 + (-4 * -4 + p * -4) = 3p 12 + (16 + -4p) = 3p Combine like terms: 12 + 16 = 28 28 + -4p = 3p Solving 28 + -4p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 28 + -4p + -3p = 3p + -3p Combine like terms: -4p + -3p = -7p 28 + -7p = 3p + -3p Combine like terms: 3p + -3p = 0 28 + -7p = 0 Add '-28' to each side of the equation. 28 + -28 + -7p = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -7p = 0 + -28 -7p = 0 + -28 Combine like terms: 0 + -28 = -28 -7p = -28 Divide each side by '-7'. p = 4 Simplifying p = 4
| 18.4-6.2x=7.24 | | 9x+3y=15 | | 5x-4y=18 | | 5x+7=19+3x | | 9x-4+6x+14=-35 | | -3x+5y=-20 | | 9x-4+6x+14=-39 | | X*2-3x-4=0 | | 2(1.5n+4)-6n=-7 | | 4x+1=2x+5 | | 3x+6x-12=4(2x-3)+x | | x^4+22x^2+21=0 | | 12x+12=13x+3 | | 5x+2=9x-4 | | x+(x+38)+(4x-40)=770 | | 5(x-3)=15 | | 73-4x=14x+23 | | 124.13=41.69+22.90x | | 6-10x=91-45x | | 27d-17=24 | | 6+9x=62+x | | -46-7x=7x+24 | | x+5=-3x-7 | | -7=7-2r | | 78+88+x=234 | | -6x+5=-7x+3 | | 8x+10=-2 | | 2x+5=-17-9x | | 9p+8=-7 | | -7+6x=2x-7 | | x-4=-26-x | | x-9=5x-57 |